Excessive Weight Gain Before and During Gestational Diabetes Mellitus Management: What Is the Impact? - Robyn A. Barnes; Tang Wong; Glynis P. Ross; Michelle M. Griffiths; Carmel E. Smart; Clare E. Collins; Lesley MacDonald‐Wicks; Jeff R. Flack (2019)
OBJECTIVE Conventional gestational diabetes mellitus (GDM) management focuses on managing blood glucose in order to prevent adverse outcomes. We hypothesized that excessive weight gain at first presentation with GDM (excessive gestational weight gain [EGWG]) and continued EGWG (cEGWG) after commencing GDM management would increase the risk of adverse outcomes, despite treatment to optimize glycemia. RESEARCH DESIGN AND METHODS Data collected prospectively from pregnant women with GDM at a single institution were analyzed. GDM was diagnosed on the basis of Australasian Diabetes in Pregnancy Society 1998 guidelines (1992–2015). EGWG means having exceeded the upper limit of the Institute of Medicine–recommended target ranges for the entire pregnancy, by GDM presentation. The relationship between EGWG and antenatal 75-g oral glucose tolerance test (oGTT) values and adverse outcomes was evaluated. Relationships were examined between cEGWG, insulin requirements, and large-for-gestational-age (LGA) infants. RESULTS Of 3,281 pregnant women, 776 (23.6%) had EGWG. Women with EGWG had higher mean fasting plasma glucose (FPG) on oGTT (5.2 mmol/L [95% CI 5.1–5.3] vs. 5.0 mmol/L [95% CI 4.9–5.0]; P < 0.01), after adjusting for confounders, and more often received insulin therapy (47.0% vs. 33.6%; P < 0.0001), with an adjusted odds ratio (aOR) of 1.4 (95% CI 1.1–1.7; P < 0.01). aORs for each 2-kg increment of cEGWG were a 1.3-fold higher use of insulin therapy (95% CI 1.1–1.5; P < 0.001), an 8-unit increase in final daily insulin dose (95% CI 5.4–11.0; P < 0.0001), and a 1.4-fold increase in the rate of delivery of LGA infants (95% CI 1.2–1.7; P < 0.0001). CONCLUSIONS The absence of EGWG and restricting cEGWG in GDM have a mitigating effect on oGTT-based FPG, the risk of having an LGA infant, and insulin requirements.